The Use of Agricultural Technology in Rural Papua: A Rural Sociological Analysis and Global Comparison - Therresse Nofianti; Fadli Zainuddin; Krisnawati (West Science Agro, 2026)
This article reviews the literature related to the application of agricultural technology in rural Papua and West Papua using a rural sociology perspective. This study has three main objectives: (1) to examine various national and international literature on agricultural technology in rural Papua, (2) to highlight the social, cultural, and structural factors that influence technology adoption among farmers, and (3) to compare local research findings with international studies to formulate a technology implementation model that is more relevant to local conditions. The analysis shows that technologies such as superior seeds, biotechnology-based fertilizers, simple mechanization, and the digitization of agricultural information can increase productivity by up to 30%. However, these benefits are not evenly distributed due to obstacles such as limited infrastructure, low digital literacy, and dependence on external inputs. Compared with countries such as Vietnam, China, and Kenya, which have recorded 40–45% increases through the use of precision technology and pro-farmer policy support, Papua still lags behind. Social factors such as the leadership of traditional leaders, cultural factors such as local wisdom and resistance to modernisation, and structural factors such as access to extension services and financing are key to successful adoption. Therefore, agricultural development in Papua requires a combination of technological innovation with local knowledge, strengthening social networks, and inclusive, participatory, and sustainable policies.